A community-led mobile health clinic to improve structural and social determinants of health among (im)migrant workers - Shannon Guillot-Wright; N. Miles Farr; Ellie Cherryhomes (BMC, 2022)
Abstract Background Community-led interventions that address structural and social determinants of health are lacking among (im)migrant workers, especially seafood workers. This lack of medical attention is especially alarming given their high rate of injury and death. Methods Community-based participatory research (CBPR), a relational model that values the participants as equal partners in research, dissemination, and implementation, guided the interviews and mobile clinic. Seafood workers were engaged throughout data collection, analysis, and interpretation and played a significant role in moving the findings from research into actionable change. Results To address the lack of healthcare options for (im)migrants, and at the request of the seafood workers participating in the ongoing CBPR study, we successfully implemented and treated workers in our mobile clinic. Discussion Many of these individuals had not been seen by a healthcare provider in years, highlighting the importance of community trust and rapport building when addressing interconnected health and safety issues. Conclusions Although CBPR and free (mobile) health clinics are in and of themselves not novel concepts, when applied to high-risk occupational settings with under-reached populations (e.g., (im)migrant workers), they have the ability to improve health and prevent injury. This intervention adds to the growing literature detailing the potential benefits of using CBPR, and meeting people where they are, especially with historically marginalized populations.